Directed assembly of fluidic networks by buckle delamination of films on patterned substrates - Moon, Myoung-Woon; Chung, Seok; Lee, Kwang-Ryeol; Oh, Kyu Hwan; Stone, Howard A.; Hutchinson, John W. (CARL HANSER VERLAG, 2007)
A method to create networks of intricate fluidic channels formed from metals and ceramics is proposed and demonstrated. The method exploits buckle delamination of a thin compressed film bonded to a substrate. A low adhesion layer coinciding with the desired layout of the channel network is laid down prior to deposition of the film. Once triggered, the buckle delamination propagates along the low adhesion pathways driven by release of the elastic energy stored in the film, assembling the entire channel network without external intervention. Strips, tapered strips and a selection of grids are demonstrated for diamond-like carbon films bonded to Si substrates with gold providing low adhesion. Control of the film thickness (15 mn to 260 nm) and the width of the low adhesion regions (200 mn to microns) enables the cross-sectional area of the channel to be defined precisely with height determined by the buckle amplitude (40 nm to 500 nm). The channel network has been integrated with a microfluidic interface formed from polydimethylsiloxane. Pressure-driven flow of two miscible streams shows convectively enhanced mixing in these nanoscale buckled channels.
Keywords: COMPRESSED THIN-FILMS; DNA-MOLECULES; MICROCHANNEL; GOLD; NANOCHANNELS; STABILITY; COATINGS; RELEASE; DEVICES; WATER